Penerapan Digital Marketing dan Teknologi Alat Pemintal Benang Tenun Otomatis Ramah Lingkungan pada Pengrajin Lurik Mulyo Cawas Klaten Jawa Tengah - Adhianty Nurjanah; Linda Kusumastuti Wardana; Wahyudi Wahyudi; Riski Apriliani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Dusun Tegalmulyo Cawas Klaten, Central Java, is one of the centers for producing striated weaving using Non-Machine Weaving Equipment (ATBM). ATBM, owned by craftsmen, is a legacy from their predecessors and has been running for decades, including Kreasi's partner and Lurik Weaving Craftsman "Lurik Mulyo." Producing the woven fabric requires five stages and is carried out manually: dyeing and evaporation of yarn, spinning, arranging motifs, weaving, and finishing. Partners currently do not have direct customers; sales presently being made are sales through middlemen. So that if there are no middlemen who order, then the two partners will not get income, especially in conditions of the Covid-19 pandemic like this. The two partners also have no bargaining value because the middleman determines the selling price. Therefore, the expansion of the marketing area with the direct selling method through a digital marketing platform is one of the solutions offered in this program. The next problem is the inefficient and effective production process because it is done manually and can encourage high production costs. Therefore, the service team offers a solution by applying environmentally friendly automatic spinner technology by combining energy sources from solar cells and household electricity sources. The non-academic outcomes that will be achieved through this program are an increase in spinning process capacity to double, which is then patented, an increase in turnover by 50%, and an increase in direct customers by 50%.